(untitled) (Journal of Environmental Science and Natural Resources, 2013)
This study presented community based framework to assess the risk and the adaptation practice as response to climate change and different disasters. The communitys experience suggested risks are shifting along with prolongation of hydro-meteorological events and its irregularity is threatening adaptation capacities as it is affecting the sensitivity and production of the ecosystem of the region. In this study, community identified flash flood, flood, wave erosion; river bank erosion and water pollution were as common hazards and risks of their life as well as community identified and assessed their seasonal calendar and livelihood activities, element at risk, problem matrix ranking/ priority, risk evaluation, causes of risks and their adaptation. In this viewpoint, some recommendations were suggested for community to adaptation, practices and conservation of wetland. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14807 J. Environ. Sci. & Natural Resources, 5(2): 161-166 2012